Hot melt adhesive sheet
The hot-melt adhesive sheet with a crosslinked polyurethane-epoxy-isocyanate composition addresses resistance and adhesion issues by using a polyester urethane resin with an aromatic skeleton, achieving enhanced resistance and adhesion properties.
Patent Information
- Application Number
- CN202380041322.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-17
- Publication Date
- 2024-12-31
AI Technical Summary
Existing hot-melt adhesive sheets lack sufficient resistance to moisture, heat, acid, and alcohol, and do not ensure strong adhesion to adherends.
A hot-melt adhesive sheet comprising a substrate with an adhesive layer formed from a crosslinked composition of a polyurethane resin, an epoxy resin, and an isocyanate crosslinking agent, where the polyurethane resin contains a polyester urethane with an aromatic polyester skeleton, and the epoxy resin has a specific epoxy equivalent range, enhancing resistance and adhesion.
The adhesive layer exhibits improved hot water resistance, acid resistance, alcohol resistance, and strong adhesion to various substrates, maintaining mechanical integrity under stress.
Smart Images

Figure CN119234021A_ABST
Abstract
Description
[0001] Cross-references of related applications
[0002] This application claims the priority of Japanese Patent Application No. 2022-087187, the disclosure of which is incorporated by reference into the description of the present application specification. Technical Field
[0003] The present invention relates to a hot-melt adhesive sheet. Background Art
[0004] In the past, polyurethane adhesives have been widely used as adhesives for various plastics due to their excellent adhesion stability in low temperature ranges (e.g., -10°C to 15°C), adhesion in normal temperature ranges (25±10°C), flexibility, processability, and ease of various molecular designs.
[0005] As the aforementioned polyurethane-based adhesive, there are the following adhesives: a polyurethane-based adhesive containing polyester polyol or acrylic polyol as a main agent and polyisocyanate as a cross-linking agent, and a cross-linking reaction is carried out between the aforementioned main agent and the aforementioned cross-linking agent to generate urethane bonds; a polyurethane-based adhesive containing a polyurethane having a certain chain length (so-called polyurethane prepolymer) as a main agent and an isocyanate-based cross-linking agent as a cross-linking agent, and a cross-linking reaction is carried out between the aforementioned main agent and the aforementioned cross-linking agent and cured.
[0006] In addition, regarding a two-component adhesive containing a polyurethane resin as a main component and containing an epoxy resin and an isocyanate-based crosslinking agent, Patent Document 1 listed below describes an adhesive having excellent moisture and heat resistance.
[0007] In recent years, there are increasing opportunities to use hot melt adhesives for bonding members from the viewpoint of being superior in handling properties compared to liquid adhesives such as those described in Patent Document 1 listed below.
[0008] In particular, the hot-melt adhesive is often used in the form of a hot-melt adhesive sheet from the viewpoint of excellent handling properties.
[0009] The hot-melt adhesive sheet generally includes a base layer formed of a polymer sheet and an adhesive layer formed of the hot-melt adhesive laminated on the base layer.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: International Publication No. 2013 / 157604 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] Improved resistance to moisture and heat (hot water resistance) is required not only for the two-component adhesive described in Patent Document 1 but also for the adhesive layer of the hot-melt adhesive sheet.
[0015] Furthermore, the adhesive layer of the hot-melt adhesive sheet is required to have improved acid resistance, alcohol resistance, etc., but such requirements have not yet been met.
[0016] Furthermore, the adhesive layer of the hot-melt adhesive sheet is also required to be able to sufficiently ensure adhesion to an adherend by thermocompression bonding.
[0017] The present invention has been made in view of the problems of the prior art, and an object of the present invention is to provide a hot-melt adhesive sheet having an adhesive layer having excellent adhesion to an adherend and excellent hot water resistance, acid resistance, and alcohol resistance.
[0018] Solutions for solving problems
[0019] The hot-melt adhesive sheet according to the present invention is a hot-melt adhesive sheet comprising a substrate and an adhesive layer laminated on at least one side of the substrate, wherein the adhesive layer is formed of a hot-melt adhesive.
[0020] The hot melt adhesive contains a crosslinked product of an adhesive composition containing a crosslinking agent, wherein the adhesive composition contains a polyurethane resin, an epoxy resin, and an isocyanate crosslinking agent.
[0021] The polyurethane resin contains a polyester urethane resin having an aromatic polyester skeleton,
[0022] The epoxy resin contains a non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic cross-sectional view showing the structure of a hot-melt adhesive sheet according to one embodiment of the present invention.
[0024] Figure 2 This is a schematic cross-sectional view showing a state in which a hot-melt adhesive sheet according to one embodiment of the present invention is attached to a solid electrolyte membrane of a polymer electrolyte fuel cell for use. DETAILED DESCRIPTION
[0025] Hereinafter, a hot-melt adhesive sheet according to an embodiment of the present invention will be described with reference to the drawings.
[0026] Hereinafter, one embodiment of the present invention may be simply referred to as the present embodiment.
[0027] like Figure 1As shown, the hot-melt adhesive sheet 10 of the present embodiment includes a base material 10a and an adhesive layer 10b laminated on at least one surface of the base material 10a, and the adhesive layer 10b is formed of a hot-melt adhesive.
[0028] Figure 1 In the hot-melt adhesive sheet 10 shown, the adhesive layer 10b may be laminated only on one surface of the base material 10a, but the adhesive layer 10b may be laminated on the other surface of the base material 10a.
[0029] That is, the hot-melt adhesive sheet 10 may be a hot-melt adhesive sheet in which the adhesive layer 10 b is laminated on both surfaces of the base material 10 a .
[0030] In the hot-melt adhesive sheet 10 of the present embodiment, the hot-melt adhesive contains a crosslinked product of an adhesive composition containing a crosslinking agent, and the adhesive composition contains a polyurethane resin, an epoxy resin, and an isocyanate-based crosslinking agent.
[0031] In the hot-melt adhesive sheet 10 of the present embodiment, the polyurethane resin contains a polyester urethane resin having an aromatic polyester skeleton.
[0032] In the hot-melt adhesive sheet 10 of the present embodiment, the epoxy resin contains a non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less.
[0033] Hereinafter, the polyurethane resin is referred to as a polyurethane resin (A), the epoxy resin is referred to as an epoxy resin (B), and the isocyanate-based crosslinking agent is referred to as an isocyanate-based crosslinking agent (C).
[0034] (Polyurethane resin (A))
[0035] The polyurethane resin (A) is obtained by urethane bonding reaction components including a polyol component (a) having two or more hydroxyl groups in one molecule and a polyisocyanate component (b) having two or more isocyanate groups in one molecule.
[0036] As described above, in the hot-melt adhesive sheet 10 of the present embodiment, the polyurethane resin (A) contains a polyester urethane resin having an aromatic polyester skeleton.
[0037] In the present specification, the polyester urethane resin refers to a resin obtained by reacting a hydroxyl-containing polyester having a hydroxyl group (corresponding to the above-mentioned polyol component (a)) with a polyisocyanate component (b).
[0038] That is, in the present specification, the polyester urethane resin is a urethane bonded product of a hydroxyl-containing polyester having a hydroxyl group and a polyisocyanate component (b).
[0039] As the hydroxyl group-containing polyester, polyester obtained by a condensation reaction of a polycarboxylic acid and a polyol can be used.
[0040] Examples of the polycarboxylic acid include phthalic acid, isophthalic acid, terephthalic acid, maleic acid, itaconic acid, fumaric acid, tetrahydrophthalic acid, hexahydrophthalic acid, adipic acid, sebacic acid, azelaic acid, trimellitic acid, methylcyclohexenetricarboxylic acid or pyromellitic acid, dimer acids derived from unsaturated fatty acids, and anhydrides thereof.
[0041] Examples of the polyol include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, 1,4-butanediol, 1,3-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol.
[0042] Furthermore, the polyol may be a polyol having a carboxyl group (hereinafter also referred to as a carboxyl group-containing polyol).
[0043] Examples of the carboxyl group-containing polyol include dimethylol propionic acid, dimethylol butyric acid, and diphenolic acid.
[0044] Furthermore, the polyol may be modified with a caprolactone compound such as ε-caprolactam.
[0045] Examples of the polyisocyanate component (b) to be reacted with the hydroxyl group-containing polyester include aliphatic isocyanate compounds, alicyclic isocyanate compounds, and aromatic isocyanate compounds.
[0046] Examples of the aliphatic isocyanate compound include hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, and xylylene diisocyanate.
[0047] Examples of the alicyclic isocyanate compound include isophorone diisocyanate, methylcyclohexane diisocyanate, lysine diisocyanate, and cyclohexane-1,4-diisocyanate.
[0048] Examples of the aromatic isocyanate compound include tolylene diisocyanate, 1,5-naphthalene diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-diphenyldimethylmethane diisocyanate, 4,4′-dibenzyl diisocyanate, tetraalkyldiphenylmethane isocyanate, dialkyldiphenylmethane diisocyanate, 1,3′-phenylene diisocyanate, and 1,4′-phenylene diisocyanate.
[0049] Here, in the hot-melt adhesive sheet 10 of the present embodiment, the polyester urethane resin is a polyester urethane resin having an aromatic polyester skeleton.
[0050] When obtaining the hydroxyl group-containing polyester, by using phthalic acid, isophthalic acid, terephthalic acid or the like as the polycarboxylic acid, the polyester urethane resin can be provided with the aromatic polyester skeleton.
[0051] As described above, if the polyester urethane resin has an aromatic polyester skeleton, the polyester urethane resin exhibits high hydrophobicity, and therefore the hydrophobicity of the adhesive layer 10 b containing such a polyester urethane resin is improved.
[0052] Thereby, the adhesive layer 10b becomes excellent in hot water resistance, acid resistance, and alcohol resistance.
[0053] Examples of commercially available products of the polyester urethane resin include VYLON (registered trademark) UR series manufactured by Toyobo Co., Ltd.
[0054] Among the VYLON (registered trademark) UR series manufactured by Toyobo Co., Ltd., VYLON (registered trademark) UR-3200 and UR-3210 are preferably used as commercially available products.
[0055] It should be noted that VYLON (registered trademark) UR-3210 is a toluene-free product of VYLON (registered trademark) UR-3200.
[0056] Therefore, from the viewpoint of reducing the amount of volatile organic compounds (VOC) generated as much as possible, it is preferable to use VYLON (registered trademark) UR-3210 as a commercially available product.
[0057] The polyester urethane resin having an aromatic polyester skeleton more preferably has a glass transition temperature Tg of 10° C. or less.
[0058] Since the polyester urethane resin having an aromatic polyester skeleton has the above-described structure, when included in the adhesive layer 10 b , the adhesive layer 10 b can exhibit good adhesion to an adherend such as the substrate 10 a .
[0059] Examples of the substrate 10 a include a PEN (polyethylene naphthalate) film, a perfluorocarbon sulfonic acid resin sheet (film), and a PPS (polyphenylene sulfide) film.
[0060] Furthermore, the polyester urethane resin has the above-mentioned configuration, so that the toughness of the adhesive layer 10 b becomes excellent.
[0061] Therefore, even when an external force is applied to the adhesive layer 10b, the adhesive layer 10b is less likely to be broken.
[0062] The glass transition temperature Tg is more preferably 5°C or lower, further preferably 0°C or lower, and further preferably -2°C or lower.
[0063] Furthermore, the glass transition temperature is preferably -30°C or higher, more preferably -20°C or higher, further preferably -10°C or higher, and further preferably -5°C or higher.
[0064] It should be noted that VYLON (registered trademark) UR-3200 and UR-3210 have an aromatic polyester skeleton and a glass transition temperature Tg of 10° C. or less.
[0065] The glass transition temperature Tg can be measured using, for example, a DSC apparatus.
[0066] More specifically, the glass transition temperature Tg can be determined from a DSC curve obtained when the temperature of a sample (polyester urethane resin) is increased at a rate of 5°C / min while nitrogen is flowing from a temperature 30K or more lower than the expected glass transition temperature Tg to a temperature 30K or more higher than the expected glass transition temperature Tg.
[0067] The glass transition temperature Tg can be determined according to the method described in JIS K7121: 1987 "Methods for determining transition temperatures of plastics".
[0068] The polyurethane resin (A) may contain a polyurethane resin other than the polyester urethane resin.
[0069] As the polyurethane resin other than the polyester urethane resin, various known resins can be used, but as the polyol component (a), it is preferred that the polyol component (a) contains a structural unit derived from a polyol (a1) having 8 or more carbon atoms in the skeleton.
[0070] The polyurethane resin other than the polyester urethane resin preferably contains a hydroxyl-containing polyurethane resin having a hydroxyl group in order to react with the isocyanate crosslinking agent (C).
[0071] Furthermore, the hydroxyl-containing polyurethane resin preferably has a hydroxyl group at a terminal.
[0072] The hydroxyl value of the hydroxyl-containing polyurethane resin is preferably 0.1 mgKOH / g or more and 20 mgKOH / g or less, and more preferably 1 mgKOH / g or more and 15 mgKOH / g or less.
[0073] In the polyurethane resin other than the polyester urethane resin, the polyol component (a) more preferably contains a common polyol (a2) together with the polyol (a1) having 8 or more carbon atoms in the backbone.
[0074] In addition, below, a normal polyol (a2) may be simply referred to as a polyol (a2).
[0075] In the present specification, the polyol (a1) having 8 or more carbon atoms in the skeleton refers to a polyol having 8 or more carbon atoms between hydroxyl groups, and refers to a polyol in which the 8 or more carbon atoms between hydroxyl groups may be bonded via a hetero atom, or adjacent carbon atoms may be saturatedly bonded or unsaturatedly bonded to each other.
[0076] The polyol (a1) having a carbon number of 8 or more in the skeleton is preferably a polycarbonate polyol.
[0077] Furthermore, in the polyol (a1) having 8 or more carbon atoms in the skeleton, the number of heteroatoms contained in the portion having 8 or more carbon atoms is preferably 2 or less.
[0078] Furthermore, the polyol (a1) having 8 or more carbon atoms in the skeleton preferably contains a residue obtained by removing a plurality of hydrogen atoms from a saturated or unsaturated hydrocarbon having 8 or more carbon atoms in the molecule.
[0079] Furthermore, the polyol (a1) having a carbon number of 8 or more in the skeleton preferably has an alkylene group having a carbon number of 6 or more.
[0080] Examples of the polyol (a1) having a carbon number of 8 or more in the skeleton include polyester polyols obtained by polycondensing monomers containing dicarboxylic acids (sebacic acid (carbon number 10), azelaic acid (carbon number 9), isophthalic acid (carbon number 8), terephthalic acid (carbon number 8) and the like) and diols (1,9-nonanediol (carbon number 9), 1,4-bishydroxymethylcyclohexane (carbon number 8) and the like).
[0081] Examples of the polyol (a1) having a backbone carbon number of 8 or more include polycarbonate polyols such as poly(1,4-cyclohexanedimethylene carbonate) diol (carbon number 8), polyoctamethylene carbonate diol (carbon number 8), polynonamethylene carbonate diol (carbon number 9), and polydecamethylene carbonate diol (carbon number 10), and random / block copolymers containing monomers thereof.
[0082] Examples of the polyol (a1) having a carbon number of 8 or more in the skeleton include polyols derived from dimer acids.
[0083] The dimer acid is a dicarboxylic acid having 36 carbon atoms obtained by dimerizing an unsaturated fatty acid having 18 carbon atoms, such as oleic acid and linoleic acid, and is a fatty acid derived from plants.
[0084] The representative structure of the dimer acid is shown in the following formula (1).
[0085] The dimer acid may contain a trimer acid.
[0086] Trimer acid is a tricarboxylic acid having 54 carbon atoms obtained by trimerizing the above-mentioned unsaturated fatty acid having 18 carbon atoms. It is also produced as a by-product during the production of dimer acid, and commercially available dimer acid generally contains trimer acid.
[0087]
[0088] The dimer diol which is a polyol derived from a dimer acid is a polyol having 36 carbon atoms obtained by reducing the carboxyl groups of the dimer acid to hydroxyl groups.
[0089] The polyol may or may not have an unsaturated bond in its molecule.
[0090] Specific examples of such dimer polyols include dimer diol and the like.
[0091] Trimer triol is also a polyol obtained by reducing the carboxyl groups of trimer acid to hydroxyl groups.
[0092] Commercially available dimer diols usually contain trimer triols.
[0093] Thus, polyols derived from dimer acids, dimer polyols, and dimer diols may contain trimer triols.
[0094] Examples of the polyol (a1) having a carbon number of 8 or more in the skeleton include polyolefin polyols.
[0095] The polyolefin polyol is a polymer obtained by polymerizing one or more polyolefins having a plurality of hydroxyl groups.
[0096] Specific examples of such polyolefin polyols include polyethylene butene diol, polybutadiene diol, and hydrogenated polybutadiene diol.
[0097] These are polyols with extremely long carbon chains due to the polymerization of carbon chains.
[0098] In the adhesive layer 10b of the hot-melt adhesive sheet 10, by including, as the polyurethane resin (A), a polyurethane resin having a structural unit derived from a polyol (a1) having a carbon number of 8 or more in the skeleton as described above (specifically, a polyurethane resin other than the aforementioned polyester urethane resin), the hydrophobicity of the adhesive layer 10b can be improved compared to a resin containing a structural unit not having a polyol (a1) having a carbon number of 8 or more in the skeleton.
[0099] Therefore, the adhesive layer 10 b has excellent hot water resistance, acid resistance, and alcohol resistance.
[0100] As the polyol (a2), a conventionally known polyol used in the synthesis of a polyurethane resin can be used.
[0101] Specific examples of the polyol (a2) include polyester polyol, polyether polyol, polycarbonate polyol, and other polyols.
[0102] Examples of the polyester polyol include those obtained by polycondensation of aliphatic dicarboxylic acids (eg, succinic acid, adipic acid, glutaric acid, etc.) and low molecular weight diols (eg, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, etc.).
[0103] The polyester polyol described above may be copolymerized with a dicarboxylic acid or a diol having 8 or more carbon atoms.
[0104] Specific examples of such polyester polyols include polyethylene adipate diol, polybutylene adipate diol, polyhexamethylene adipate diol, polyneopentyl adipate diol, polyethylene adipate / butylene adipate diol, polyneopentyl adipate / hexanediol adipate diol, poly3-methylpentane adipate diol, polybutylene isophthalate diol, polycaprolactone diol, and poly-3-methylvalerolactone diol.
[0105] Compared with polyether polyols, polyester polyols have better heat resistance.
[0106] Therefore, polyester polyol is more advantageous than polyether polyol in that the obtained adhesive layer 10b is an adhesive layer having excellent heat resistance.
[0107] Specific examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and random / block copolymers thereof.
[0108] Compared with polyester polyols, polyether polyols have better hydrolysis resistance.
[0109] Therefore, polyether polyol is more advantageous than polyester polyol in that the obtained adhesive layer 10b is an adhesive layer having excellent hydrolysis resistance.
[0110] Specific examples of the polycarbonate polyol include polytetramethylene carbonate diol, polypentamethylene carbonate diol, polyneopentyl carbonate diol, polyhexamethylene carbonate diol, and random / block copolymers thereof.
[0111] The above-mentioned polycarbonate polyol may be copolymerized with a diol having 8 or more carbon atoms.
[0112] By using the above-mentioned various polycarbonate diols as the polycarbonate polyol, a polyurethane resin other than the above-mentioned polyester urethane resin can be provided with a carbonate diol structural unit.
[0113] Here, polycarbonate polyol is excellent in hydrolysis resistance and heat resistance.
[0114] Therefore, it is advantageous from the viewpoint of making the obtained adhesive layer 10 b excellent in hydrolysis resistance and heat resistance.
[0115] Among the polycarbonate polyols, polyhexamethylene carbonate diol is preferred from the viewpoint of cost and availability of materials.
[0116] Specific examples of other polyols include acrylic polyols, epoxy polyols, polyether ester polyols, silicone-modified polyols, α,ω-polymethyl methacrylate diol, α,ω-polybutyl methacrylate diol, and silicone-modified polyols.
[0117] Summarizing the above description about the polyol (a2), from the viewpoint of improving the hot water resistance of the adhesive layer 10 b of the obtained hot-melt adhesive sheet 10 , it is preferable to use a polycarbonate polyol having excellent hydrolysis resistance and heat resistance.
[0118] Among the above-mentioned polycarbonate polyols, polyhexamethylene carbonate diol is particularly preferably used from the viewpoint of cost and availability of materials.
[0119] The number average molecular weight Mn (measured by a terminal functional group quantitative method) of the polyol (a1) and the polyol (a2) is not particularly limited, but is preferably 500 or more and 6,000 or less.
[0120] When the number average molecular weight Mn of the polyol (a1) and the polyol (a2) is within the above numerical range, the cohesive force due to the urethane bond is easily expressed in the adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment.
[0121] Therefore, the adhesive according to the present embodiment has high mechanical properties.
[0122] Furthermore, when the number average molecular weight Mn of the crystalline polyol is too large, when the adhesive layer 10 b is formed into a coating film, the adhesive layer 10 b may whiten.
[0123] Therefore, when a crystalline polyol is used alone as the polyol (a1) and the polyol (a2), it is preferred to use a crystalline polyol having a number average molecular weight Mn of 3,000 or less.
[0124] In addition, the said polyol (a1) and the said polyol (a2) may be used individually by 1 type, or may use 2 or more types together.
[0125] The polyol (a1) is preferably blended in a ratio of 10% by mass to 60% by mass, based on 100% by mass of the polyol component (a).
[0126] By blending the polyol (a1) at a ratio of 10% by mass or more, the hot melt adhesive of the present embodiment can have sufficient hot water resistance, acid resistance, and alcohol resistance.
[0127] Furthermore, by blending the polyol (a1) in an amount of 60% by mass or less, the compatibility of the urethane resin (A) and the epoxy resin (B) can be improved, and the obtained hot-melt adhesive can have excellent adhesion to polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, and resin film formed from a perfluorocarbon sulfonic acid resin.
[0128] It should be noted that when the aforementioned polyol component (a) is a copolymer of a monomer having a backbone carbon number of 8 or more and a monomer having a backbone carbon number of 7 or less, the mass parts of the monomer having a backbone carbon number of 8 or more are calculated as the mass parts of the aforementioned polyol (a1), and the mass parts of the monomer having a backbone carbon number of 7 or less are calculated as the mass parts of the aforementioned polyol (a2).
[0129] As the polyol component (a), in addition to the polyol (a1) and the polyol (a2), a short-chain diol (a3) may be used as necessary.
[0130] Specific examples of the short-chain diol (a3) include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol, and low-molecular weight alkylene oxide adducts thereof (the number average molecular weight Mn measured by the terminal functional group quantitative method is less than 500); alicyclic diols such as 1,4-bishydroxymethylcyclohexane and 2-methyl-1,1-cyclohexanedimethanol, and low-molecular weight alkylene oxide adducts thereof (the number average molecular weight Mn is less than 500, as above); aromatic diols such as benzyl alcohol or low-molecular weight alkylene oxide adducts thereof (the number average molecular weight Mn is less than 500, as above); bisphenols such as bisphenol A, sulfonated bisphenol, and sulfone bisphenol, and low-molecular weight alkylene oxide adducts thereof (the number average molecular weight Mn is less than 500, as above), and the like.
[0131] Among the above-mentioned short-chain diols (a3), ethylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol and the like are preferably used, and ethylene glycol, 1,3-butanediol and 1,4-butanediol are particularly preferably used.
[0132] These short-chain diols (a3) may be used alone or in combination of two or more.
[0133] When a polyurethane resin other than the polyester urethane resin is produced, a polyol compound can be used as a material for the polyurethane resin other than the polyester urethane resin, similarly to the short-chain diol (a3).
[0134] Specific examples of the polyol compound include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, tris-(2-hydroxyethyl)isocyanurate, 1,1,1-trimethylolethane, and 1,1,1-trimethylolpropane.
[0135] If necessary, a hydroxyl group-containing compound (a4) having a carboxyl group may also be used.
[0136] The hydroxyl group-containing compound (a4) having a carboxyl group usually has two or more hydroxyl groups in one molecule.
[0137] The hydroxyl-containing compound (a4) having a carboxyl group generally has two or more hydroxyl groups in one molecule, and thus can react with a polyisocyanate component (b) having two or more isocyanate groups in one molecule to obtain a polyurethane resin.
[0138] Examples of the hydroxyl-containing compound (a4) having a carboxyl group include dimethylolpropionic acid, dimethylolbutanoic acid, low-molar addition products of alkylene oxides thereof (number average molecular weight Mn less than 500), low-molar addition products of γ-caprolactone (number average molecular weight Mn less than 500), half esters derived from an acid anhydride and glycerol, and compounds derived from a free radical reaction between a monomer containing a hydroxyl group and an unsaturated group and a monomer containing a carboxyl group and an unsaturated group.
[0139] Among these various compounds, dimethylolpropionic acid and dimethylolbutanoic acid are preferably used, and dimethylolpropionic acid is particularly preferably used.
[0140] These compounds may be used alone or in combination of two or more.
[0141] Here, the number average molecular weight Mn refers to a value measured by a terminal functional group quantitative method.
[0142] It should be noted that the above-mentioned various compounds are examples of preferred compounds in the present invention.
[0143] Therefore, the hydroxyl group-containing compound (a4) having a carboxyl group used in the present invention is not limited to the above-mentioned various compounds.
[0144] Therefore, in addition to the above-mentioned various compounds, any hydroxyl group-containing compound (a4) having a carboxyl group that is currently commercially available and can be easily obtained from the market can be used in the present invention.
[0145] As the polyisocyanate component (b), a conventionally known polyisocyanate component used in the production of a polyurethane resin can be used.
[0146] Specific examples of the polyisocyanate component (b) include toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, mixtures thereof, 4-methoxy-1,3-phenylene diisocyanate, 4-isopropyl-1,3-phenylene diisocyanate, 4-chloro-1,3-phenylene diisocyanate, 4-butoxy-1,3-phenylene diisocyanate, 2,4-diisocyanate diphenyl ether, 4,4'-methylenebis(phenylene isocyanate) (MDI), crude or polymerized MDI, durylenediisocyanate, xylylene diisocyanate (XDI), 1,5-naphthalene Aromatic diisocyanates such as diisocyanate, benzidine diisocyanate, o-nitrobenzidine diisocyanate, and 4,4-dibenzyl diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 1,10-decamethylene diisocyanate; alicyclic diisocyanates such as 1,4-cyclohexylene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,5-tetrahydronaphthalene diisocyanate, isophorone diisocyanate, and hydrogenated XDI; polyurethane prepolymers obtained by reacting these diisocyanates with low molecular weight polyols in a manner that the ends become isocyanates, etc.
[0147] Among these polyisocyanate components (b), aromatic isocyanates are preferably used from the viewpoint of being able to stably obtain the adhesive layer 10b of the hot-melt adhesive sheet 10 which is inexpensive and has excellent heat resistance industrially, and toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, a mixture thereof, 4,4'-methylenebis(phenylene isocyanate) (MDI), and crude or polymerized MDI are particularly preferably used.
[0148] By using an aromatic isocyanate as the polyisocyanate component (b), a structural unit of an aromatic diisocyanate can be provided in a polyurethane resin other than the polyester urethane resin.
[0149] These polyisocyanate components (b) may be used alone or in combination of two or more.
[0150] (Method for producing polyurethane resin (A))
[0151] Regarding the method for producing the polyurethane resin (A), the method for producing the polyester urethane resin (A) will be described below first, and then the method for producing the polyurethane resin other than the polyester urethane resin (A) will be described.
[0152] The polyester urethane resin can be produced by reacting a polyisocyanate component (b) with a hydroxyl group-containing polyester.
[0153] The reaction of the hydroxyl group-containing polyester and the polyisocyanate component (b) can be carried out by a conventionally known method.
[0154] As described above, in the hot-melt adhesive sheet 10 of the present embodiment, the polyester urethane resin has an aromatic polyester skeleton.
[0155] The polyester urethane resin can be made a resin having an aromatic polyester skeleton by using phthalic acid, isophthalic acid, terephthalic acid or the like as the polycarboxylic acid when obtaining the hydroxyl-containing polyester.
[0156] The polyurethane resin other than the polyester urethane resin can be produced by a conventionally known method for producing polyurethane.
[0157] Hereinafter, a method for producing a polyurethane resin other than a polyester urethane resin using a polyol (a1) having a carbon number of 8 or more in the backbone will be described.
[0158] Even when the polyol (a1) having 8 or more carbon atoms in the backbone is not used, a polyurethane resin other than the polyester urethane resin can be produced in the same manner as described below.
[0159] First, a reaction composition comprising the polyol (a1) having 8 or more carbon atoms in the skeleton, the polyol (a2), the polyisocyanate component (b) and, if necessary, a short-chain diol (a3) as a chain extender as a reaction component is reacted in the presence or absence of an organic solvent containing no active hydrogen in the molecule, thereby obtaining a polyurethane resin other than a polyester urethane resin.
[0160] When obtaining a polyurethane resin other than the polyester urethane resin, the hydroxyl group-containing compound (a4) having a carboxyl group may be used as necessary.
[0161] The reaction composition can generally be set to a blending composition in which the equivalent ratio of the isocyanate group to the hydroxyl group is 0.8 to 1.25.
[0162] The reaction can be carried out by a one-shot method or a multi-stage method at usually 20 to 150°C, preferably 60 to 110°C.
[0163] The mass average molecular weight Mw of the polyurethane resin other than the polyester urethane resin obtained as described above is preferably 1,000 or more and 100,000 or less.
[0164] When the mass average molecular weight Mw is within the above numerical range, the hot-melt adhesive containing the polyurethane resin (A) can more effectively exhibit properties such as adhesion to a substrate, hot water resistance, acid resistance, and alcohol resistance.
[0165] In addition, the mass average molecular weight Mw of the polyurethane resin other than the said polyester urethane resin is the value measured by gel permeation chromatography (GPC).
[0166] The mass average molecular weight Mw of the polyurethane resin other than the polyester urethane resin can be measured, for example, by the following apparatus and conditions.
[0167] Measurement equipment and measurement conditions
[0168] · Equipment: Trade name "HLC-8020" (manufactured by TOSOH)
[0169] Column: Trade names "TSKgel G2000HXL", "G3000HXL", "G4000GXL" (manufactured by TOSOH)
[0170] Solvent: THF
[0171] Flow rate: 1.0ml / min
[0172] Sample concentration: 2g / L
[0173] Injection volume: 100μL
[0174] Temperature: 40℃
[0175] Detector: Model "RI-8020" (manufactured by TOSOH)
[0176] ·Standard material: TSK standard polystyrene (manufactured by TOSOH)
[0177] In the present embodiment, a catalyst may be used as necessary in the synthesis of the polyester urethane resin and the polyurethane resin other than the polyester urethane resin.
[0178] Examples of the catalyst include salts of metals such as dibutyltin laurate, dioctyltin laurate, stannous octoate, zinc octoate, tetra-n-butyl titanate, and organic or inorganic acids, organometallic derivatives, organic amines such as triethylamine, and diazabicycloundecene-based catalysts.
[0179] The catalyst can promote the synthesis reaction of the polyester urethane resin and a polyurethane resin other than the polyester urethane resin.
[0180] On the other hand, if the catalyst is used excessively, a decomposition reaction may be induced to decompose the polyester urethane resin and substances other than the polyurethane resin other than the polyester urethane resin, and as a result, the long-term heat resistance of the obtained hot melt adhesive may be deteriorated.
[0181] Therefore, when the catalyst is used, it is preferred to use an appropriate amount of the catalyst.
[0182] The polyester urethane resin and the polyurethane resin other than the polyester urethane resin may be synthesized without using an organic solvent or may be synthesized using an organic solvent.
[0183] As the organic solvent, an organic solvent that is inactive with respect to isocyanate groups or an organic solvent that is less active with respect to isocyanate groups than the reaction component can be used.
[0184] Specific examples of the aforementioned organic solvent include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbon solvents such as toluene, xylene, Swasol (trade name, manufactured by Cosmo Oil Co., Ltd.), and Solvesso (trade name, manufactured by Exxon Mobil Co., Ltd.); aliphatic hydrocarbon solvents such as n-hexane; alcohol solvents such as methanol, ethanol, and isopropanol; ether solvents such as dioxane and tetrahydrofuran; ester solvents such as ethyl acetate, butyl acetate, and isobutyl acetate; carbonate solvents such as dimethyl carbonate, diethyl carbonate, and ethylene carbonate; glycol ether ester solvents such as ethylene glycol ethyl ether acetate, propylene glycol methyl ether acetate, 3-methyl-3-methoxybutyl acetate, and ethyl-3-ethoxypropionate; amide solvents such as dimethylformamide and dimethylacetamide; lactam solvents such as N-methyl-2-pyrrolidone, etc.
[0185] Toluene, methyl ethyl ketone, and ethyl acetate are particularly preferred from the viewpoint of improving the solubility of the polyurethane resin and facilitating volatilization when obtaining a hot-melt adhesive.
[0186] (Epoxy resin (B))
[0187] As described above, the epoxy resin (B) contains a non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less.
[0188] The epoxy equivalent may be 350 g / eq or more, or 400 g / eq or more.
[0189] Furthermore, the epoxy equivalent may be 1000 g / eq or less.
[0190] It should be noted that the unmodified epoxy resin refers to an epoxy resin that has not been modified with rubber or the like.
[0191] In addition, the said epoxy equivalent is the value calculated|required based on JIS K7236.
[0192] Examples of the non-modified epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol AD epoxy resin.
[0193] Among these non-modified epoxy resins, bisphenol A type epoxy resin is preferably used.
[0194] Examples of commercially available bisphenol A-type epoxy resins having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less include trade names “JER 1001” (epoxy equivalent of 450 to 500 g / eq), “JER 1002” (epoxy equivalent of 600 to 700 g / eq), “JER 1003” (epoxy equivalent of 670 to 770 g / eq), “JER 1055” (epoxy equivalent of 800 to 900 g / eq), “JER 1004” (epoxy equivalent of 875 to 975 g / eq), and “JER 1004AF” (epoxy equivalent of 875 to 975 g / eq) manufactured by Mitsubishi Chemical Corporation.
[0195] In addition, the above-mentioned non-modified epoxy resin may be used alone or in combination of two or more.
[0196] The epoxy resin (B) may contain a rubber-modified epoxy resin in addition to the above-mentioned non-modified epoxy resin.
[0197] The adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment contains the rubber-modified epoxy resin as the epoxy resin (B) in addition to the non-modified epoxy resin. Therefore, even when the adhesive layer 10b is attached to an adherend (e.g., a PEN film, a perfluorocarbon sulfonic acid resin sheet, a PPS film, etc.), it is easy to suppress the adhesive layer 10b from peeling off from the adherend even after being immersed in 95°C hot water, 95°C dilute sulfuric acid (pH 2), or 95°C water-ethylene glycol mixed solution (the mixing ratio of ethylene glycol is 50 volume%) for a long time such as 1000 hours.
[0198] It should be noted that the rubber-modified epoxy resin is a compound having at least one epoxy group in the molecule and having a structure derived from rubber.
[0199] The rubber-modified epoxy resin may be used alone or in combination of two or more.
[0200] Examples of the rubber-modified epoxy resin include a reaction product of a non-modified epoxy resin and a rubber.
[0201] As the non-modified epoxy resin, for example, the bisphenol A type epoxy resin, the bisphenol F type epoxy resin, the bisphenol AD type epoxy resin, etc. can be used.
[0202] By setting the epoxy equivalent of the non-modified epoxy resin to 300 g / eq or more and 1500 g / eq or less, the non-modified epoxy resin can be cross-linked at an appropriate cross-linking density in the cross-linking reaction using the isocyanate cross-linking agent (C).
[0203] Thereby, the adhesive layer 10b including the non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less can exhibit sufficient adhesiveness to an adherend.
[0204] If the epoxy equivalent of the unmodified epoxy resin exceeds 1500 g / eq, the amount of epoxy groups per unit mass becomes insufficient, and thus the unmodified epoxy resin cannot be crosslinked with sufficient crosslinking density in the crosslinking reaction using the isocyanate crosslinking agent (C).
[0205] Therefore, when the adhesive layer 10b contains the non-modified epoxy resin having an epoxy equivalent exceeding 1500 g / eq, the adhesive layer 10b cannot obtain sufficient strength, which is not preferable.
[0206] If the epoxy equivalent of the unmodified epoxy resin is less than 300 g / eq, the amount of epoxy groups per unit mass becomes too large, and thus the crosslinking density of the unmodified epoxy resin becomes too high in the crosslinking reaction using the isocyanate crosslinking agent (C).
[0207] Therefore, when the adhesive layer 10b contains the unmodified epoxy resin having an epoxy equivalent of less than 300 g / eq, the crosslinking density of the adhesive layer 10b based on the unmodified epoxy resin becomes too high and becomes hard and brittle, resulting in insufficient adhesion to the adherend, which is not preferred.
[0208] Examples of the rubber include natural rubber, acrylonitrile butadiene rubber (NBR), carboxyl-terminated acrylonitrile butadiene rubber (CTBN), amino-terminated acrylonitrile butadiene rubber (ATBN), styrene butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR), ethylene-propylene rubber (EPDM), acrylic rubber (ACM), butyl rubber (IIR), butadiene rubber, and the like.
[0209] From the viewpoint of reactivity with epoxy groups, the rubber preferably has a functional group such as an amino group, a hydroxyl group or a carboxyl group that is reactive with an epoxy group at a terminal.
[0210] From the viewpoint of easy availability and reactivity with epoxy groups, the rubber-modified epoxy resin is preferably a reaction product of an epoxy resin and acrylonitrile butadiene rubber (NBR) (NBR-modified epoxy resin), a reaction product of an epoxy resin and a carboxyl-terminated acrylonitrile butadiene rubber (CTBN-modified epoxy resin), or a reaction product of an epoxy resin and an amino-terminated acrylonitrile butadiene rubber (ATBN-modified epoxy resin), among which NBR-modified epoxy resin is particularly preferred.
[0211] In addition, as a commercial product of the said NBR modified epoxy resin, the trade name "ADEKA RESIN EPR-1415-1" manufactured by ADEKA Corporation is mentioned.
[0212] The method for producing the rubber-modified epoxy resin is not particularly limited as long as it is a method capable of reacting the epoxy resin with the rubber, and various known production methods can be employed.
[0213] The physical properties of the rubber-modified epoxy resin are not particularly limited, but from the viewpoint of handling properties, adhesive properties, etc., a rubber-modified epoxy resin having an epoxy equivalent of 150 g / eq or more and 1000 g / eq is preferred.
[0214] The epoxy resin (B) may be contained in an amount of 10 parts by mass or more, 20 parts by mass or more, or 30 parts by mass or more, based on 100 parts by mass of the polyurethane resin (A).
[0215] Moreover, the epoxy resin (B) may be contained in an amount of 60 parts by mass or less, or 50 parts by mass or less, based on 100 parts by mass of the polyurethane resin (A).
[0216] Furthermore, in the epoxy resin (B), the non-modified epoxy resin is preferably contained in an amount of 10 parts by mass or more, more preferably 20 parts by mass or more, based on 100 parts by mass of the polyurethane resin (A).
[0217] The non-modified epoxy resin is preferably contained in an amount of 40 parts by mass or less, more preferably 30 parts by mass or less, based on 100 parts by mass of the polyurethane resin (A).
[0218] Furthermore, in the epoxy resin (B), the rubber-modified epoxy resin is preferably contained in an amount of 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the polyurethane resin (A).
[0219] The rubber-modified epoxy resin is preferably contained in an amount of 30 parts by mass or less, more preferably 20 parts by mass or less, based on 100 parts by mass of the polyurethane resin (A).
[0220] Furthermore, when the epoxy resin (B) contains both the unmodified epoxy resin and the rubber-modified epoxy resin, the mass ratio of the unmodified epoxy resin to the mass ratio of the rubber-modified epoxy resin may be 1.1 or more, 1.2 or more, or 1.3 or more.
[0221] Furthermore, the ratio of the mass ratio of the non-modified epoxy to the mass ratio of the rubber-modified epoxy may be 3.0 or less, 2.0 or less, or 1.5 or less.
[0222] (Isocyanate crosslinking agent (C))
[0223] The isocyanate crosslinking agent (C) is not particularly limited, and conventionally used known isocyanate crosslinking agents having a polyfunctional isocyanate group such as an isocyanurate form, a biuret form, an adduct, or a polymer can be used.
[0224] For example, there can be mentioned dimers of 2,4-toluene diisocyanate, triphenylmethane triisocyanate, tris-(p-isocyanatephenyl)thiophosphite, polyfunctional aromatic isocyanates, polyfunctional aromatic aliphatic isocyanates, polyfunctional aliphatic isocyanates, fatty acid-modified polyfunctional aliphatic isocyanates, blocked polyisocyanates such as blocked polyfunctional aliphatic isocyanates, and polyisocyanate prepolymers.
[0225] Among these isocyanate crosslinking agents (C), if they are aromatic isocyanate crosslinking agents, diphenylmethane diisocyanate, toluene diisocyanate, and xylylene diisocyanate are preferred.
[0226] In the case of an aliphatic isocyanate-based crosslinking agent, modified products such as hexamethylene diisocyanate and isophorone diisocyanate are preferred.
[0227] Furthermore, as the isocyanate-based crosslinking agent (C), an isocyanate-based crosslinking agent containing three or more isocyanate groups in one molecule is preferred.
[0228] Furthermore, as the isocyanate crosslinking agent (C), it is also preferable to use a polymer of the above-mentioned polyisocyanate, an adduct with other compounds, and a urethane prepolymer obtained by reacting a low molecular weight polyol with a polyamine so that the molecular terminal becomes an isocyanate.
[0229] Among the various isocyanate-based crosslinking agents (C) described above, xylylene diisocyanate is preferably used.
[0230] As a commercial product of the said xylylene diisocyanate, the trade name "TAKENATE D-110N" manufactured by Mitsui Takeda Chemicals Co., Ltd. is mentioned, for example.
[0231] The adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment preferably contains 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 7 parts by mass of the isocyanate crosslinking agent (C) based on 100 parts by mass of the polyurethane resin (A).
[0232] The isocyanate crosslinking agent (C) is contained in an amount of preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the polyurethane resin (A).
[0233] In the adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment, by containing the aforementioned isocyanate-based crosslinking agent (C) in the above-mentioned mass ratio, even when the adhesive layer 10b is attached to an adherend (for example, a PEN film, a perfluorocarbon sulfonic acid resin sheet, a PPS film, etc.), it is possible to suppress the adhesive layer 10b from peeling off from the aforementioned adherend even after being immersed in 95°C hot water, 95°C dilute sulfuric acid (pH 2), or 95°C water-ethylene glycol mixed solution (the mixing ratio of ethylene glycol is 50 volume%) for a long time such as 1000 hours.
[0234] That is, the adhesive layer 10b of the hot-melt adhesive sheet 10 is an adhesive layer excellent in long-term hot water resistance, long-term acid resistance, and long-term alcohol resistance.
[0235] The present inventors speculate as follows about the reason why the adhesive layer 10 b of the hot-melt adhesive sheet 10 of the present embodiment is excellent in adhesion to an adherend and is also excellent in hot water resistance, acid resistance, and alcohol resistance.
[0236] As described above, the adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment is formed by a hot-melt adhesive, which contains a polyester urethane resin having an aromatic polyester skeleton as a polyurethane resin (A), contains a non-modified epoxy resin (bisphenol A type epoxy resin, etc.) with an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less as an epoxy resin (B), and contains an isocyanate-based cross-linking agent (C).
[0237] In the adhesive layer 10 b , the polyester urethane resin having an aromatic polyester skeleton and the non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less are crosslinked by an isocyanate crosslinking agent (C).
[0238] That is, in the adhesive layer 10b of the hot-melt adhesive sheet 10 of this embodiment, the polyester urethane resin having an aromatic polyester skeleton and the unmodified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less are contained in a state crosslinked by an isocyanate crosslinking agent (C).
[0239] Here, as described above, the polyester urethane resin having an aromatic polyester skeleton exhibits high hydrophobicity.
[0240] Therefore, the adhesive layer 10 b contains the polyester urethane resin having an aromatic polyester skeleton, thereby improving the hydrophobicity of the adhesive layer 10 b.
[0241] Therefore, it is considered that the adhesive layer 10b becomes an adhesive layer excellent in hot water resistance, acid resistance, and alcohol resistance.
[0242] When the epoxy equivalent of the unmodified epoxy resin contained in the adhesive layer 10b is 300 g / eq or more and 1500 g / eq or less, the unmodified epoxy resin is crosslinked at an appropriate crosslinking density in the adhesive layer 10b by the isocyanate crosslinking agent (C).
[0243] Therefore, it is considered that the adhesive layer 10b exhibits good adhesiveness to the adherend.
[0244] From the above, it is considered that the adhesive layer 10b of the hot-melt adhesive sheet 10 of the present embodiment is excellent in adhesion to an adherend, and is also excellent in hot water resistance, acid resistance, and alcohol resistance.
[0245] Next, refer to Figure 2 Further description will be given by taking an example in which the adherend to which the adhesive layer 10 b of the hot melt sheet 10 of the present embodiment is bonded is a membrane electrode assembly (MEA) 20 of a polymer electrolyte fuel cell.
[0246] The adherend membrane / electrode assembly (MEA) 20 is configured to allow hydrogen gas to permeate from the negative electrode side to the positive electrode side and to generate electricity by reacting oxygen supplied to the positive electrode side with the hydrogen.
[0247] like Figure 2 As shown, in a membrane electrode assembly (MEA) 20 , a positive electrode 202 and a negative electrode 203 are stacked on two opposing surfaces of a solid electrolyte membrane 201 .
[0248] The positive electrode 202 includes a positive electrode catalyst layer 202 a and a positive electrode gas diffusion layer 202 b stacked on the positive electrode catalyst layer 202 a . The positive electrode catalyst layer 202 a is stacked on one surface of the solid electrolyte membrane 201 .
[0249] The negative electrode 203 includes a negative electrode catalyst layer 203 a and a negative electrode gas diffusion layer 203 b stacked on the negative electrode catalyst layer 203 a . The negative electrode catalyst layer 203 a is stacked on the other surface of the solid electrolyte membrane 201 .
[0250] like Figure 2As shown, the positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a are formed in a manner that the planar size is smaller than that of the solid electrolyte membrane 201, and the positive electrode gas diffusion layer 202b and the negative electrode gas diffusion layer 203b are formed in a manner that the planar size is smaller than that of the positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a.
[0251] That is, in the membrane electrode assembly (MEA), the planar dimensions of the positive electrode 202 and the negative electrode 203 are smaller than the planar dimension of the solid electrolyte membrane 201 .
[0252] By making the planar size of the positive electrode 202 smaller than the planar size of the solid electrolyte membrane 201 as described above, the solid electrolyte membrane 201 extends to the outside of the positive electrode catalyst layer 202a on the positive electrode side (one side) of the membrane / electrode assembly (MEA) 20, and the positive electrode side electrolyte membrane exposed area 201a of the exposed surface of the solid electrolyte membrane 201 is formed on the periphery.
[0253] In addition, since the planar size of the negative electrode 203 is smaller than the planar size of the solid electrolyte membrane 201, on the negative electrode side (the other side) of the membrane / electrode assembly (MEA) 20, the solid electrolyte membrane 201 extends to the outside of the negative electrode catalyst layer 203a, and the negative electrode side electrolyte membrane exposed area 201b of the exposed surface of the solid electrolyte membrane 201 is formed on the periphery.
[0254] Furthermore, on the positive electrode side of the membrane / electrode assembly (MEA) 20, the positive electrode catalyst layer 202a extends to the outside of the positive electrode gas diffusion layer 202b to form a positive electrode side catalyst layer exposed region 202a1 where the surface of the positive electrode catalyst layer 202a is exposed.
[0255] The positive electrode side catalyst layer exposed region 202a1 is formed inside the positive electrode side electrolyte membrane exposed region 201a and outside the positive electrode gas diffusion layer 202b.
[0256] In the present embodiment, the positive electrode side electrolyte membrane exposed region 201 a is formed in a ring shape so as to surround the outer periphery of the membrane / electrode assembly (MEA) 20 .
[0257] The positive electrode side catalyst layer exposed region 202a1 is formed in a ring shape smaller than the positive electrode side electrolyte membrane exposed region 201a.
[0258] That is, on the positive electrode side of the membrane / electrode assembly (MEA), a second boundary L2 belonging to the boundary between the positive electrode side catalyst layer exposed area 202a1 and the positive electrode gas diffusion layer 202b is formed on the inner side of the first boundary L1 belonging to the boundary between the positive electrode side electrolyte membrane exposed area 201a and the positive electrode side catalyst layer exposed area 202a1.
[0259] On the negative electrode side of the membrane / electrode assembly (MEA) 20, the negative electrode catalyst layer 203a extends to the outside of the negative electrode gas diffusion layer 203b to form a negative electrode side catalyst layer exposed region 203a1 where the surface of the negative electrode catalyst layer 203a is exposed.
[0260] The negative electrode side catalyst layer exposed region 203a1 is formed inside the negative electrode side electrolyte membrane exposed region 201b and outside the negative electrode gas diffusion layer 203b.
[0261] In the present embodiment, the negative electrode side electrolyte membrane exposed region 201 b is formed in a ring shape so as to surround the outer periphery of the membrane / electrode assembly (MEA) 20 .
[0262] The negative electrode side catalyst layer exposed region 203a1 is formed in a ring shape smaller than the negative electrode side electrolyte membrane exposed region 201b.
[0263] That is, on the negative electrode side of the membrane / electrode assembly (MEA) 20, a fourth boundary L4, which is the boundary between the negative electrode side catalyst layer exposed area 203a1 and the negative electrode gas diffusion layer 203b, is formed on the inner side of the third boundary L3, which is the boundary between the negative electrode side electrolyte membrane exposed area 201b and the negative electrode side catalyst layer exposed area 203a1.
[0264] exist Figure 2 In the usage state shown, the two hot-melt adhesive sheets 10, namely the first hot-melt adhesive sheet 10 bonded to the positive electrode side of the membrane / electrode assembly (MEA) 20 and the second hot-melt adhesive sheet 10 bonded to the negative electrode side of the membrane / electrode assembly (MEA) 20, are used as auxiliary gasket materials for solid polymer fuel cells.
[0265] The first hot-melt adhesive sheet 10 is annular and has a shape in which the outer edge becomes the outside of the membrane / electrode assembly (MEA) 20 when overlapped on the membrane / electrode assembly (MEA) 20 and the inner edge is contained in the positive electrode side catalyst layer exposed area 202a1 and the negative electrode side catalyst layer exposed area 203a1.
[0266] That is, the hollow portion of the first hot-melt adhesive sheet 10 has a shape slightly larger than the positive electrode gas diffusion layer 202 b .
[0267] The second hot-melt adhesive sheet 10 also has the same shape as the first hot-melt adhesive sheet 10 .
[0268] In the present embodiment, the first hot-melt adhesive sheet 10 and the second hot-melt adhesive sheet 10 are directly bonded to the outer peripheral portion of the adhesive layer 10 b on the outer side of the membrane electrode assembly (MEA) 20 , and are used as the auxiliary gasket material.
[0269] In the first hot-melt adhesive sheet 10, the inner peripheral portion other than the outer peripheral portion bonded to the second hot-melt adhesive sheet 10 is bonded to the outer peripheral portion of the membrane / electrode assembly (MEA) 20, and is bonded to the range from the positive electrode side electrolyte membrane exposed area 201a across the first boundary line L1 to the positive electrode side catalyst layer exposed area 202a1.
[0270] The second hot-melt adhesive sheet 10 is also bonded to the first hot-melt adhesive sheet 10 in the same manner.
[0271] By bonding (adhering) the hot-melt adhesive sheet 10 to the membrane / electrode assembly (MEA) 20 as described above, a portion of the positive electrode gas can pass through the positive electrode side electrolyte membrane exposed area 201a, and a portion of the negative electrode gas can pass through the negative electrode side electrolyte membrane exposed area 201b, thereby suppressing the performance degradation of the solid polymer fuel cell.
[0272] As described above, in a polymer electrolyte fuel cell, hydrogen and oxygen react in the membrane electrode assembly (MEA) 20 to generate electricity.
[0273] Furthermore, as described above, when hydrogen and oxygen react, the membrane / electrode assembly (MEA) 20 reaches a relatively high temperature (eg, 95° C.).
[0274] When the aforementioned solid polymer fuel cell is installed as a power source for an automobile, the central portion of the membrane / electrode assembly (MEA) 20 can be sufficiently cooled by circulating the antifreeze liquid contained in the water tank through the pipes, but the aforementioned pipes are usually not configured to the edge portions of the membrane / electrode assembly (MEA) 20, so the edge portions of the membrane / electrode assembly (MEA) 20 will continue to maintain a high temperature.
[0275] When the antifreeze liquid is circulated, part of the antifreeze liquid may leak out of the pipe, and the antifreeze liquid leaked from the pipe may come into contact with the adhesive layer 10 b attached to the edge side of the solid electrolyte membrane 201 .
[0276] The antifreeze solution generally contains polyethylene glycol and water as liquid components. Therefore, in such a case, the adhesive layer 10 b is in contact with the polyethylene glycol and water at high temperature.
[0277] Furthermore, as explained above, in the reaction that generates electricity, hydrogen ions (H + ) will cause mass transfer in the membrane / electrode assembly (MEA) 20, so the membrane / electrode assembly (MEA) 20 will show strong acidity equivalent to about 0.1 to 0.5M dilute sulfuric acid.
[0278] In such a case, the adhesive layer 10 b attached to the edge side of the solid electrolyte membrane 201 is exposed to strong acidity at high temperature.
[0279] Here, in the hot-melt adhesive sheet 10 of the present embodiment, the adhesive layer 10b is configured as described above, and therefore the adhesive layer 10b is excellent in long-term hot water resistance, long-term acid resistance, and long-term alcohol resistance.
[0280] Therefore, when the hot melt adhesive sheet of this embodiment is used as an auxiliary gasket material in a solid polymer fuel cell installed in an automobile, as described above, even if the adhesive layer 10b comes into contact with water or alcohol at a high temperature of 95°C, or the adhesive layer 10b is exposed to a strong acid at a high temperature of 95°C, it can maintain adhesion to the solid electrolyte membrane 201 for a long time (1000 hours).
[0281] As will be described later, the solid electrolyte membrane 201 is generally a solid electrolyte membrane formed of a fluororesin such as perfluorocarbon sulfonic acid.
[0282] It should be noted that in the membrane / electrode assembly (MEA) 20, the positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a are generally formed using a catalyst ink composition containing a catalyst supporting material such as a carbon material supporting a catalyst, a proton conductive polymer, and a solvent.
[0283] The solid electrolyte membrane 201 of the membrane electrode assembly (MEA) 20 is formed of, for example, a fluororesin such as a perfluorocarbon sulfonic acid resin.
[0284] Examples of the perfluorocarbon sulfonic acid resin include "Nafion" manufactured by DuPont, "Flemion" manufactured by Asahi Kasei Corporation, and "Aciplex" manufactured by Asahi Glass Co., Ltd.
[0285] The perfluorocarbon sulfonic acid resin is, for example, a resin having a polymer structure represented by the following formula (1).
[0286] Regarding m, n and x in the following formula (1), for example, in the aforementioned "Nafion", m≥1, n=2, x=5-13.5, in the aforementioned "Aciplex", m=0,1, n=2-5, x=1.5-14, and in the aforementioned "Flemion", m=0,1, n=1-5.
[0287]
[0288] The positive electrode catalyst layer 202a and the negative electrode catalyst layer 203a are layers containing catalyst particles.
[0289] Examples of the catalyst particles contained in the positive electrode catalyst layer 202 a include platinum.
[0290] Examples of the catalyst particles contained in the negative electrode catalyst layer 203 a include platinum compounds.
[0291] Examples of the platinum compound include alloys of platinum and at least one metal selected from the group consisting of ruthenium, palladium, nickel, molybdenum, iridium, and iron.
[0292] The positive electrode gas diffusion layer 202b and the negative electrode gas diffusion layer 203b are formed of a porous conductive base material.
[0293] Examples of the porous conductive substrate include carbon paper and carbon cloth.
[0294] Furthermore, the hot-melt adhesive sheet 10 of the present embodiment can also be used in a redox flow battery.
[0295] Hot melt adhesive sheets used in redox flow batteries are used to suppress the permeation of electrolyte.
[0296] Matters disclosed in this specification include the following.
[0297] (1) A hot-melt adhesive sheet comprising a substrate and an adhesive layer laminated on at least one surface of the substrate, wherein the adhesive layer is formed of a hot-melt adhesive.
[0298] The hot melt adhesive contains a crosslinked product of an adhesive composition containing a crosslinking agent, wherein the adhesive composition contains a polyurethane resin, an epoxy resin, and an isocyanate crosslinking agent.
[0299] The polyurethane resin contains a polyester urethane resin having an aromatic polyester skeleton,
[0300] The epoxy resin contains a non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less.
[0301] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has excellent adhesion to an adherend and is also excellent in hot water resistance, acid resistance, and alcohol resistance.
[0302] (2) The hot-melt adhesive sheet according to the above (1), wherein the polyurethane resin further includes a polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in the skeleton.
[0303] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0304] (3) The hot-melt adhesive sheet according to the above (2), wherein the polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in its skeleton comprises a hydroxyl-containing polyurethane resin having a hydroxyl group,
[0305] The hydroxyl value of the hydroxyl-containing polyurethane resin is 0.1 mgKOH / g or more and 20 mgKOH / g or less.
[0306] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0307] (4) The hot-melt adhesive sheet according to the above (2) or (3), wherein the polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in its skeleton has an aromatic diisocyanate as a structural unit.
[0308] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0309] (5) The hot-melt adhesive sheet according to any one of (2) to (4) above, wherein the polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in its skeleton has a mass average molecular weight Mw of 1,000 to 100,000.
[0310] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0311] (6) The hot-melt adhesive sheet according to any one of (1) to (5) above, wherein the polyester urethane resin has a glass transition temperature Tg of 10° C. or less.
[0312] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0313] (7) The hot-melt adhesive sheet according to any one of (1) to (6) above, wherein the unmodified epoxy resin is a bisphenol A epoxy resin.
[0314] According to this configuration, the adhesive layer of the hot-melt adhesive sheet has better adhesion to an adherend and better hot water resistance, acid resistance, and alcohol resistance.
[0315] (8) The hot-melt adhesive sheet according to any one of (1) to (7) above, which is used by being bonded to a solid electrolyte membrane of a polymer electrolyte fuel cell.
[0316] The hot-melt adhesive sheet of the present invention is not limited to the above-mentioned embodiment. In addition, the hot-melt adhesive sheet of the present invention is not limited to the above-mentioned effects. The hot-melt adhesive sheet of the present invention can be modified in various ways within the scope of the present invention.
[0317] Example
[0318] (Example 1)
[0319] The following components were mixed in the blending ratios shown in Table 1 below to obtain a composition for a hot-melt adhesive layer of Example 1.
[0320] A polyurethane resin containing a structural unit derived from a polyol (a1) having 8 or more carbon atoms in the backbone (hereinafter also referred to as polyurethane resin A1)
[0321] Polyester urethane resin (trade name "VYLON (registered trademark) UR-3210" manufactured by Toyobo Co., Ltd.; hereinafter also referred to as polyurethane resin A2)
[0322] Bisphenol A type epoxy resin: "JER1001" manufactured by Mitsubishi Chemical Corporation (epoxy equivalent: 450 to 500 g / eq. hereinafter also referred to as epoxy resin B1)
[0323] Rubber-modified epoxy resin (trade name "ADEKA RESIN EPR-1415-1" manufactured by ADEKA Corporation. Hereinafter, also referred to as epoxy resin B2)
[0324] Isocyanate crosslinking agent (C) (trade name "TAKENATED-110N" manufactured by MITSUI TAKEDA CHEMICALS, INC.)
[0325] In addition, the polyurethane resin A1 used was a resin synthesized as follows, and the epoxy resin B1 was dissolved and used as follows.
[0326] [Synthesis of polyurethane resin A1]
[0327] A reaction vessel equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen blowing tube, and a manhole was prepared.
[0328] While the interior of the reaction container was replaced with nitrogen, 300.0 g of polyhexamethylene carbonate diol having hydroxyl groups at both ends (DURANOL: T6002, manufactured by Asahi Kasei Chemicals Corporation), 200.0 g of polycyclohexanedimethanol / hexanediol copolycarbonate diol (trade name "ETERNACOLLUM-90 (3 / 1)", manufactured by Ube Industries, Ltd., hydroxyl value = 112.2 mgKOH / g, cyclohexanedimethanol / hexanediol = 3 / 1 molar ratio), and 10.0 g of 1,3-butanediol were added.
[0329] Next, 207.3 g of methyl ethyl ketone (MEK) was added as a solvent, and the system was stirred.
[0330] After the system became uniform, 111.8 g of 4,4′-diphenylmethane diisocyanate (MDI) was added at 50° C., and the mixture was reacted at 80° C. to obtain a reaction liquid.
[0331] The reaction solution was diluted with methyl ethyl ketone (MEK) to adjust the viscosity of the reaction solution, and the reaction was continued until the free isocyanate group-derived carbonyl group reached 2,270 cm-1 as measured by infrared absorption spectroscopy. -1 The reaction mixture was stirred for 2 hours until the absorption at the position disappeared, thereby obtaining a resin solution AA1 containing the polyurethane resin A1.
[0332] The solid content of the obtained resin solution AA1 was 30% by mass, the hydroxyl value of the polyurethane resin A1 was 2.5 mgKOH / g, and the polyol (a1) having 8 or more carbon atoms in the skeleton was 29.7% by mass.
[0333] The mass average molecular weight of the polyurethane resin A1 measured by GPC was 72,000.
[0334] [Dissolution of epoxy resin B1]
[0335] A reaction vessel equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen blowing tube, and a manhole was prepared.
[0336] While the inside of the reaction container was replaced with nitrogen, 400.0 g of epoxy resin B1 (JER1001) was added, and 600.0 g of methyl ethyl ketone (MEK) as a solvent was added while stirring.
[0337] Thereafter, the temperature in the system was raised to 60° C. to completely dissolve the epoxy resin B1, thereby obtaining a dissolved product BB1 of the epoxy resin B1 (hereinafter referred to as epoxy resin solution BB1).
[0338] The solid content of the obtained epoxy resin solution BB1 was 40% by mass.
[0339] In addition, if it demonstrates in more detail, the composition for hot-melt adhesive layers of Example 1 was obtained as follows.
[0340] (1) The resin solution AA1 and the epoxy resin solution BB1 were mixed so that the polyurethane resin A1 and the epoxy resin B1 were in the blending ratio shown in Table 1 below to obtain a mixed solution.
[0341] (2) To the mixed solution, polyurethane resin A2 (polyester urethane resin), epoxy resin B2 (rubber-modified epoxy resin) and isocyanate crosslinking agent (C) were added according to the compounding ratios shown in Table 1 below.
[0342] (3) The polyurethane resin A2, the epoxy resin B2 and the isocyanate crosslinking agent (C) are completely dissolved in the mixed solution.
[0343] [Table 1]
[0344]
[0345] (Example 2)
[0346] A composition for a hot-melt adhesive layer of Example 2 was obtained in the same manner as in Example 1 except that the epoxy resin B2 was not added.
[0347] (Example 3)
[0348] A hot melt adhesive layer composition of Example 3 was obtained in the same manner as in Example 1 except that Mitsubishi Chemical Corporation's trade name "JER1003" (epoxy equivalent: 670 to 770 g / eq) was used instead of Mitsubishi Chemical Corporation's trade name "JER1001" as the bisphenol A type epoxy resin.
[0349] (Example 4)
[0350] A composition for a hot-melt adhesive layer of Example 4 was obtained in the same manner as in Example 3 except that the epoxy resin B2 was not added.
[0351] (Example 5)
[0352] A hot melt adhesive layer composition of Example 5 was obtained in the same manner as in Example 1 except that Mitsubishi Chemical Corporation's trade name "JER1004" (epoxy equivalent: 875 to 975 g / eq) was used instead of Mitsubishi Chemical Corporation's trade name "JER1001" as the bisphenol A type epoxy resin.
[0353] (Example 6)
[0354] A composition for a hot-melt adhesive layer of Example 6 was obtained in the same manner as in Example 5 except that the epoxy resin B2 was not added.
[0355] (Comparative Example 1)
[0356] A hot melt adhesive layer composition of Comparative Example 1 was obtained in the same manner as in Example 1 except that Mitsubishi Chemical Corporation's trade name "JER1007" (epoxy equivalent: 1750 to 2200 g / eq) was used instead of Mitsubishi Chemical Corporation's trade name "JER1001" as the bisphenol A type epoxy resin.
[0357] (Comparative Example 2)
[0358] A composition for a hot-melt adhesive layer of Comparative Example 2 was obtained in the same manner as in Comparative Example 1 except that the epoxy resin B2 was not added.
[0359] (Comparative Example 3)
[0360] A hot melt adhesive layer composition of Comparative Example 3 was obtained in the same manner as in Example 1 except that Mitsubishi Chemical Corporation's trade name "JER1256" (epoxy equivalent: 7500 to 8500 g / eq) was used instead of Mitsubishi Chemical Corporation's trade name "JER1001" as the bisphenol A type epoxy resin.
[0361] (Comparative Example 4)
[0362] A composition for a hot-melt adhesive layer of Comparative Example 4 was obtained in the same manner as in Comparative Example 3 except that the epoxy resin B2 was not added.
[0363] (Comparative Example 5)
[0364] A composition for a hot melt adhesive layer of Comparative Example 5 was obtained in the same manner as in Example 1, except that a novolac-type epoxy resin, "JER157S70" (epoxy equivalent 200 to 220 g / eq), manufactured by Mitsubishi Chemical Corporation, was used instead of "JER1001" manufactured by Mitsubishi Chemical Corporation, as the bisphenol A-type epoxy resin.
[0365] (Comparative Example 6)
[0366] A composition for a hot-melt adhesive layer of Comparative Example 6 was obtained in the same manner as in Comparative Example 5 except that the epoxy resin B2 was not added.
[0367] (Comparative Example 7)
[0368] A composition for a hot-melt adhesive layer of Comparative Example 7 was obtained in the same manner as in Example 1 except that no epoxy resin was added.
[0369] (Comparative Example 8)
[0370] A composition for a hot-melt adhesive layer of Comparative Example 8 was obtained in the same manner as in Comparative Example 7 except that the epoxy resin B2 was not added.
[0371] [Application of hot-melt adhesive layer composition]
[0372] The composition for hot-melt adhesive layers of each example was diluted with methyl ethyl ketone (MEK) so that the solid content might be 30% by mass.
[0373] In each example, a diluted hot-melt adhesive layer composition was applied to the entire single-sided surface of a PEN film (length: 210 mm, width: 150 mm, thickness: 100 μm, Teonex: manufactured by TOYOBO Film Solutions Co., Ltd.), dried at 100°C for 1 minute after coating, and then placed in an oven at 40°C for 48 hours for a curing reaction (cross-linking reaction) to obtain a PEN film with a hot-melt adhesive layer.
[0374] The coating was performed so that the thickness of the hot-melt adhesive layer after drying would be 20 μm.
[0375] [Preparation of the first adhesive sheet]
[0376] Two sheets of the PEN films with hot-melt adhesive layers of each example were prepared, and the two PEN films with hot-melt adhesive layers were stacked so that the hot-melt adhesive layers came into contact with each other.
[0377] Two sheets of the PEN film with a hot-melt adhesive layer of each example were bonded together by thermocompression using a laminator adjusted at 140° C. to prepare a first adhesive sheet of each example.
[0378] [Preparation of the second adhesive sheet]
[0379] The PEN film with a hot-melt adhesive layer in each example was overlapped with the perfluorocarbon sulfonic acid resin sheet in such a manner that the exposed surface of the hot-melt adhesive layer of the PEN film with a hot-melt adhesive layer in each example was in contact with one surface of a perfluorocarbon sulfonic acid resin sheet (tetrafluoroethylene / perfluoro[2-(fluorosulfonylethoxy)propyl vinyl ether] copolymer film (manufactured by DuPont, trade name "NAFION N-115")) (having the same shape as the film with a hot-melt adhesive layer).
[0380] The PEN film with a hot-melt adhesive layer of each example and the perfluorocarbon sulfonic acid resin sheet were bonded together by thermocompression using a laminator adjusted to 140° C., thereby producing a second adhesive sheet of each example.
[0381] [Hot water resistance 1]
[0382] For the first adhesive sheet of each example, a test piece of 10 mm in width × 80 mm in length was cut out from the first adhesive sheet of each example, and the test piece was immersed in hot water at 95° C. for 1000 hours. After cooling to room temperature, the hot water resistance of each test piece was evaluated according to the following criteria.
[0383] Excellent: No peeling was observed after immersion.
[0384] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0385] · No: Peeling was observed after immersion.
[0386] [Acid resistance 1]
[0387] For the first adhesive sheet of each example, a test body of 10 mm in width × 80 mm in length was cut out from the first adhesive sheet of each example, and the test body was immersed in dilute sulfuric acid of pH 2 at 95°C for 1000 hours. After cooling to room temperature, the acid resistance of each test body was evaluated using the following criteria.
[0388] Excellent: No peeling was observed after immersion.
[0389] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0390] · No: Peeling was observed after immersion.
[0391] [Alcohol resistance 1]
[0392] For the first adhesive sheet of each example, a test body of a size of 10 mm in width × 80 mm in length was cut out from the first adhesive sheet of each example, and the test body was immersed in a water-ethylene glycol mixed solution (the mixing ratio of ethylene glycol was 50 volume %) at 95°C for 1000 hours. After cooling to room temperature, the alcohol resistance of each test body was evaluated using the following criteria.
[0393] Excellent: No peeling was observed after immersion.
[0394] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0395] · No: Peeling was observed after immersion.
[0396] [Hot water resistance 2]
[0397] For the second adhesive sheet of each example, a test piece of 10 mm in width × 80 mm in length was cut out from the second adhesive sheet of each example, and the test piece was immersed in hot water at 95° C. for 1000 hours. After cooling to room temperature, the hot water resistance of each test piece was evaluated according to the following criteria.
[0398] Excellent: No peeling was observed after immersion.
[0399] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0400] · No: Peeling was observed after immersion.
[0401] For the second adhesive sheet of each example, a test body of 10 mm in width × 80 mm in length was cut out from the second adhesive sheet of each example, and the test body was immersed in dilute sulfuric acid of pH 2 at 95°C for 1000 hours. After cooling to room temperature, the acid resistance of each test body was evaluated using the following criteria.
[0402] Excellent: No peeling was observed after immersion.
[0403] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0404] · No: Peeling was observed after immersion.
[0405] [Alcohol resistance 2]
[0406] For the second adhesive sheet of each example, a test body of 10 mm in width × 80 mm in length was cut out from the second adhesive sheet of each example, and the test body was immersed in a water-ethylene glycol mixed solution (the mixing ratio of ethylene glycol was 50 volume %) at 95°C for 1000 hours. After cooling to room temperature, the alcohol resistance of each test body was evaluated using the following criteria.
[0407] Excellent: No peeling was observed after immersion.
[0408] Acceptable: After immersion, no peeling was observed, but partial floating was observed.
[0409] · No: Peeling was observed after immersion.
[0410] [Initial sealing force]
[0411] The initial adhesion of the first adhesive sheet (adhesive sheet in which a hot-melt adhesive layer was sandwiched between two PEN films) of each example was evaluated using Autograph.
[0412] A test piece having a size of 10 mm in width and 80 mm in length was cut out from the first adhesive sheet of each example, and the adhesive strength of the test piece was measured using an Autograph.
[0413] Then, the case where the adhesive strength was 3 N / 10 mm or more was evaluated as excellent, and the case where the adhesive strength was less than 3 N / 10 mm was evaluated as unacceptable.
[0414] The above evaluation results are shown in Table 2 below.
[0415] [Table 2]
[0416]
[0417] As can be seen from Table 2, in each example, the first adhesive sheet and the second adhesive sheet were all excellent in the evaluation items.
[0418] Furthermore, it can be seen that the evaluation results of the initial adhesion were also excellent in each Example.
[0419] On the other hand, it can be seen that in each comparative example, any evaluation item was either acceptable or unacceptable.
[0420] It should be noted that in Table 2, when observing the items of hot water resistance (hot water resistance 1 and hot water resistance 2), acid resistance (acid resistance 1 and 2), and alcohol resistance (alcohol resistance 1 and alcohol resistance 2) of each comparative example, it can be seen that the evaluation results of Comparative Examples 1, 3, 5, and 7 are "acceptable", while the evaluation results of Comparative Examples 2, 4, 6, and 8 are "unacceptable".
[0421] Moreover, Comparative Examples 1, 3, 5 and 7 all contain epoxy resin B2 (rubber-modified epoxy resin), whereas Comparative Examples 2, 4, 6 and 8 do not contain epoxy resin B2 (rubber-modified epoxy resin), and they differ in this point.
[0422] From this, it is presumed that the hot water resistance, acid resistance, and alcohol resistance of Comparative Examples 1, 3, 5, and 7 are improved by including the epoxy resin B2 (rubber-modified epoxy resin).
[0423] Description of Reference Numerals
[0424] 10 hot melt adhesive sheet, 20 membrane / electrode assembly (MEA), 201 solid electrolyte membrane, 202 positive electrode, 203 negative electrode,
[0425] 10a substrate, 10b adhesive layer, 201a positive electrode side electrolyte membrane exposed region, 201b negative electrode side electrolyte membrane exposed region, 202a positive electrode catalyst layer, 202b positive electrode gas diffusion layer, 203a negative electrode catalyst layer, 203b negative electrode gas diffusion layer, 202a1 positive electrode side catalyst layer exposed region, 203a1 negative electrode side catalyst layer exposed region,
[0426] L1 is the first boundary, L2 is the second boundary, L3 is the third boundary, and L4 is the fourth boundary.
Claims
1. A hot-melt adhesive sheet comprising a substrate and an adhesive layer laminated on at least one side of the substrate, wherein the adhesive layer is formed of a hot-melt adhesive. The hot melt adhesive contains a crosslinked product of an adhesive composition containing a crosslinking agent, wherein the adhesive composition contains a polyurethane resin, an epoxy resin, and an isocyanate crosslinking agent. The polyurethane resin contains a polyester urethane resin having an aromatic polyester skeleton, The epoxy resin contains a non-modified epoxy resin having an epoxy equivalent of 300 g / eq or more and 1500 g / eq or less.
2. The hot-melt adhesive sheet according to claim 1, wherein The polyurethane resin further includes a polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in the skeleton.
3. The hot-melt adhesive sheet according to claim 2, wherein The polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in the backbone includes a hydroxyl-containing polyurethane resin having a hydroxyl group, The hydroxyl value of the hydroxyl-containing polyurethane resin is 0.1 mgKOH / g or more and 20 mgKOH / g or less.
4. The hot-melt adhesive sheet according to claim 2 or 3, wherein The polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in its skeleton has an aromatic diisocyanate as a structural unit.
5. The hot-melt adhesive sheet according to any one of claims 2 to 4, wherein The polyurethane resin having a structural unit derived from a polyol having 8 or more carbon atoms in its skeleton has a mass average molecular weight Mw of 1,000 or more and 100,000 or less.
6. The hot-melt adhesive sheet according to any one of claims 1 to 5, wherein The polyester urethane resin having an aromatic polyester skeleton has a glass transition temperature Tg of 10° C. or less.
7. The hot-melt adhesive sheet according to any one of claims 1 to 6, wherein The non-modified epoxy resin is bisphenol A type epoxy resin. 8 . The hot-melt adhesive sheet according to claim 1 , which is used by being bonded to a solid electrolyte membrane of a polymer electrolyte fuel cell.
